(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background:The recently discovered adipocytokine visfatin has insulin-like properties. It lowers blood glucose and improves insulin sensitivity; however, clinical data on visfatin are limited. Objective:To evaluate the role of visfatin in GDM (gestational diabetes mellitus), we determined visfatin levels in women with GDM and healthy pregnant women. Methods:A total of 60 women were evaluated: 30 women with gestational diabetes mellitus and 30 healthy pregnant women to serve as control subjects. Serum visfatin concentrations were analyzed using an enzyme-linked immunosorbent assay the study was done in Al-Yarmouk Teaching Hospital during the period from November 2010 to March 2011. Results:Serum visfatin concentrations were significantly lower in the gestational diabetes mellitus group (0.27±0.1 ng/ml) than in the healthy control group (1.37±0.25ng/ml) (P=0.0001). Conclusions:Our results show that there are decreased concentrations of serum visfatin in gestational diabetes mellitus subjects and this may indicate that visfatin plays a role in the pathogenesis of gestational diabetes mellitus .However; further experiments are needed to clarify this role. Key Words:Visfatin, Gestational Diabetes Mellitus